The private ownership economy with a reduced consumption sphere as an economic mechanism - Lipieta, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
Let Ep be a Debreu private ownership economy in which every consumption set is contained in the proper subspace V of the commodity – price space R. Two kinds of economic mechanisms, in the sense of Hurwicz, are designed. The goals of the design are, either the modified to the subspace V, producers’ and consumers’ optimal plans (plans maximizing appropriately profits or preferences on the budget sets) which form the state of equilibrium, or the modified to the subspace V production sets. In the presented economic mechanisms, the producers’ maximal profits do not decrease, and also the consumers’ preferences and the budget sets remain unchanged.
Mathematical Economics, 2013, Nr 9 (16), s. 39-54
Keywords: Debreu economy; complementary commodities; projections; equilibrium